2015
DOI: 10.1364/oe.23.003699
|View full text |Cite
|
Sign up to set email alerts
|

Angle dependent Fiber Bragg grating inscription in microstructured polymer optical fibers

Abstract: Abstract:We report on an incidence angle influence on inscription of the Fiber Bragg Gratings in Polymethyl methacrylate (PMMA) microstructured polymer optical fibers. We have shown experimentally that there is a strong preference of certain angles, labeled ГK, over the other ones. Angles close to ГK showed fast start of inscription, rapid inscription and stronger gratings. We have also shown that gratings can be obtained at almost any angle but their quality will be lower if they are not around ГK angle. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…During the inscription, the pulse energy and the orientation of the fiber were kept stable since the energy density in the core depends on the scattering arisen from the rings structure. Six gratings were fabricated to evaluate the angle effect on each mPOF structure [33]. Figure 6(a)-6(b) shows that the 2-rings mPOF presented the best result with the highest reflected power and the shortest time and 5-rings mPOF needed much more time for grating irradiation.…”
Section: (A)-2(c)mentioning
confidence: 99%
“…During the inscription, the pulse energy and the orientation of the fiber were kept stable since the energy density in the core depends on the scattering arisen from the rings structure. Six gratings were fabricated to evaluate the angle effect on each mPOF structure [33]. Figure 6(a)-6(b) shows that the 2-rings mPOF presented the best result with the highest reflected power and the shortest time and 5-rings mPOF needed much more time for grating irradiation.…”
Section: (A)-2(c)mentioning
confidence: 99%
“…Through the comparison of 24 mPOF gratings made with random initial orientation towards the inscription beam, Bundalo et al have experimentally confirmed that there is a strong preference angle, labeled ГK, over the other ones [126,127]. Angles close to ГK showed fast start of inscription, rapid inscription and stronger gratings due to the direct access of the laser light to the fibre core.…”
Section: Techniques and Issues Of Fabricating Pof Gratingsmentioning
confidence: 99%
“…Although the control of the writing time is a complicated process, the reduction of the inscription time is the development trend for the improvement of writing efficiency. Figure 2 shows the historical evolution of inscription time of POF Bragg gratings [44,46,52,64,65,68,70,81,85,86,91,92,95,99,102,106,112,115,120,121,126,127,132,140]. …”
Section: Techniques and Issues Of Fabricating Pof Gratingsmentioning
confidence: 99%
“…When the laser is turned off, the temperature decreases and the grating becomes of a similar intensity to the first one, observing a π-phase shift. Different results are due to the impact of the orientation in micro-structured fibers [39] which leads to strong variation on the intensity of the fabricated gratings. However, similar spectral characteristics are obtained in all cases.…”
Section: Ps-fbg Fabricationmentioning
confidence: 99%